The special questions of nutrition of forest plants - Marozsán, Marianna (Acta Agraria Debreceniensis, 2010)
Some physiological effects of bacteria containing fertilizer and some wood ash were examined in the experiments. The minimization of the use of chemicals in agriculture has been an ongoing challenge. One option lies in the intenzification of soil life. The release of organic matters by the roots and bacteria play a significant role in the uptake of minerals. The main problem to usilize wood ash in agriculture is its heavy metal contents. The solubility of heavy metals is very low, therefore there is no risk to use the wood ash in the agriculture and in the horticulture according to our experiments. The wood ash and biofertilizer contains several micronutrients in an optimum composition for forestry and agricultural plants.